Effect of technology and musical sound on concentration in individualized learning: a study of covenant university students (2012)
This study assessed technological advancement and identified the effect of musical sound on concentration in individual learning in the library among Covenant University students. This was with a view to providing valuable data for Government, University management and policy makers, instructors and teachers of the use of library and comportment and parents to guide in developing Educational programs, in order to arrest the current problem of educational decadence. The Descriptive survey method was adopted for the study. The simple random and purposive sampling techniques were used in choosing the study population. Three hundred and sixty copies of questionnaire were administered to respondents. Also data were collected through the focus group discussion, oral interview, experiment on comprehension test and existing comparative literature. It was revealed that majority of students who come to the library wearing mini earpieces actually listen to music. Also findings from the study showed that it is extremely difficult to listen to music and concentrate on a learning material simultaneously. Finally, the study revealed that the result of listening to music and learning at same time is a loss of concentration on one of the activities and poor academic performance. Therefore, the study recommends among others that students should learn to engage in one activity per time, in order to maximize the time and effort they put into individual learning which is part of the reason for which they are in school and that government, University management and policy makers should promulgate a law against the use of earpieces in the library and other learning environments while instructors, teachers, librarians and Para- librarians ensure the effective implementation of same thereby, creating veritable learning environments for the world’s future leaders and great minds.